Motor control : translating research into clinical practice - Shumway-Cook, Anne 1947- (Wolters Kluwer, 2023)
Motor Control: Translating Research into Clinical Practice, 6th Edition, is the only text that bridges the gap between current and emerging motor control research and its application to clinical practice. Written by leading experts in the field, this classic resource prepares users to effectively assess, evaluate, and treat clients with problems related to postural control, mobility, and upper extremity function using today's evidence-based best practices. This extensively revised 6th Edition reflects the latest advances in research and features updated images, clinical features, and case studies to ensure a confident transition to practice. Each chapter follows a consistent, straightforward format to simplify studying and reinforce understanding of normal control process issues, age-related issues, research on abnormal function, clinical applications of current research, and evidence to support treatments used in the rehabilitation of patients with motor control problems. New and revised content in every chapter keeps students at the forefront of motor control research. Consistent, straightforward presentation simplifies studying and reinforces student's understanding of normal control process issues, age-related issues, research on abnormal function, and clinical applications of current research, including methods for assessing, evaluating, and treating clients with motor dyscontrol in each area, and research evidence that support these treatments. Lab Activities provide valuable practice applying chapter concepts. Clinical tests and measures familiarize students with the latest assessment methods and procedures; also provided is the latest research related to interpreting tests and measure results. High-quality figures clarify concepts underlying anatomy and physiology. Chapter Summaries reinforce understanding of key takeaways at a glance. Case Studies demonstrate concepts in action. Companion videos available online guide students through the application of concepts to real-life physical therapy and rehabilitation scenarios.